Student Group Translation аs а Cultural аnd Educational Practice - Shopin, Pavlo (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
This article examines collaborative student translation as a cultural and educational practice. The object of the study is an educational and cultural diplomacy project focused on the English translation of Mykhailo Liakh’s essay “Between Drahomanov and Marx: The Political Life of Lesya Ukrainka,” carried out by twelve students from Mykhailo Drahomanov State University of Ukraine. The subject of the research is the pedagogical, linguistic, and cultural dynamics of group translation as a method of learning and intercultural engagement. The purpose of the article is to determine the role of collaborative translation in developing the professional competencies and critical historical awareness of student translators, as well as to explore how such translation projects contribute to the international recognition of Ukrainian political and intellectual traditions. This study is relevant in the context of ongoing efforts to globalize Ukrainian intellectual heritage, particularly in the aftermath of Russia’s full-scale invasion. Against this backdrop, the participants approached translation both as a linguistic task and as a form of cultural diplomacy and civic engagement. The research method combines case study analysis, participant observation, and editorial critique of student drafts within the broader context of translation pedagogy and public scholarship. The research material includes the original Ukrainian text by Mykhailo Liakh, its English translation, and the iterative revisions made by students and the professor that led to the final published version. The project demonstrates that collaborative student translation can function both as a pedagogical model and as a form of cultural diplomacy, offering students the opportunity to act as mediators of national history for international audiences. Future research could explore the cultural potential of translation through the analysis of other student-translated popular texts under the author’s supervision, the role of translation in the decolonization of knowledge, the ethical integration of AI tools in translation education, and translation as civic engagement in the context of the Russo-Ukrainian War.